ANALISIS KONSEP EFISIENSI EKONOMI DALAM ISLAM: KAJIAN TERHADAP QS. AL-ISRA AYAT 26-29 - Fauzia Ulirrahmi (University of Islam Malang, 2024)
This research discusses the concept of economic efficiency from an Islamic perspective, focusing on verses QS. Al-Isra verses 26-29. Economic efficiency in Islam is analyzed through the ethical guidelines and principles contained within these verses. The findings of this study indicate that Islam emphasizes the importance of wise resource management, fair wealth distribution, ethical conduct in transactions, and a balance in the use of wealth. Economic efficiency in Islam also considers social justice and moral values, not solely focusing on profitability. Overall, the verses in QS. Al-Isra verses 26-29 provide guidance on the concept of economic efficiency in Islam, encompassing fair distribution, avoiding waste, emphasizing ethics in every economic transaction, and balancing resource allocation. These principles can help society achieve sustainable economic efficiency while considering moral and social values.